"The Great Mimicker": An Unusual Etiology of Cytopenia, Diffuse Lymphadenopathy, and Massive Splenomegaly. (22nd October 2015) - Zaarour, Mazen; Weerasinghe, Chanudi; Moussaly, Elias; Hussein, Shafinaz; Atallah, Jean-Paul
Abstract : Sarcoidosis is an idiopathic multisystem disease characterized by the formation of noncaseating granulomas. It frequently presents with pulmonary infiltrates and bilateral hilar and mediastinal lymphadenopathy. Splenic involvement is common, but massive splenomegaly is a rare occurrence. Sarcoidosis is known as "the great mimicker" (or "the great imitator") since it exhibits a myriad of symptoms, mimicking other inflammatory, infectious, and neoplastic conditions, including lymphoma. Herein, we report the case of a 44-year-old male patient who was found to have bicytopenia, hypercalcemia, diffuse lymphadenopathy, and massive splenomegaly, a constellation of findings suggestive of underlying lymphoma. Interestingly, lymph node biopsy showed noncaseating granulomas suggestive of sarcoidosis, without evidence of malignancy.